PERAN IBU 01 DALAM PENATAAN SETING PRIVASI RUMAH TINGGALNYA (Studi Kasus:Rumah Tinggal lbu-Ibu Anggota Majlis Taklim SALlMAH Yogyakarta) - Sativa, Sativa (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Abstract People need interaction control mechanism in their activities, wherever and whenever they do. This mechanism which is named as privacy, is different among individual or community, depend on their background. This study aims to analyze role of mother with Islamic background, in privacy setting arrangement in their houses. Due to of time limitation, this study is focused on territorial arrangement, as a way to reach an optimal privacy. This research uses naturalistic qualitative method that Jakes result from induction of discovered themes. The sampLe of this research are private houses of member of Persaudaraan Muslimah organization in Yogyakart2. Themes as results of this study are: occupants and their activities, area of house, variety of rooms, roOm activities, accessibility sequence to the room, main and side entrance, and role of house setting arrangement. Further, the conclusion is: 1) Mother role in territorial arrangement to· reach optimal privacy in her house is very significant. The role in initiating and implementing territorial arrangement especially refer to defense mother privacy (aural) 2) Those territorial arrangement are formed as : arrangement of accessibility sequence of rooms, character and form of border among the rooms. Those territoriality can be deviced into 4 classifications, as public space, semi public space, semi private space and private space. In special condition those territorial space can be changed depend on activity and user need. Keywords: privacy, territorial arrangement. mother role